Performance of broiler with feeding different levels of palm oil (Bangladesh Journal of Animal Science, 2014)
Six hundred day-old unsexed broiler chicks were used in a 42-day trial to compare the effects of different levels of palm oil supplementation on feed intake, weight gain, feed conversion and carcass quality of broilers. The chicks were randomly distributed following a completely randomized design in four treatment groups having three replications per treatment. Each treatment had 150 broilers with 50 broilers per replicate. Four diets were formulated using locally available ingredients as diet without oil, diets containing 2.5%, 3.0% and 3.5% palm oil. All broilers had free access to ad libitum feeding. Results indicated that, supplementation of diets with different levels of palm oil significantly (p